Prospective Evaluation of Hemostatic System Activation and Thrombin Potential in Healthy Pregnant Women with and without Factor V Leiden - Eichinger, Sabine; Weltermann, Ansgar; Philipp, Karl; Hafner, Erich; Kaider, Alexandra; Kittl, Eva-Maria; Brenner, Brigitte; Mannhalter, Christine; Lechner, Klaus; Kyrle, Paul A. (Thrombosis and Haemostasis, 1999)
Normal pregnancy is associated with alterations of the hemostatic system towards a hypercoagulable state and an increased risk of venous thromboembolism. The risk of venous thrombosis is higher in pregnant women with factor V Leiden (FVL) than in those with wildtype factor V. Routine laboratory assays are not useful to detect hypercoagulable conditions. A prospective and systematic evaluation of hemostatic system activation in women with and without FVL during an uncomplicated pregnancy employing more sensitive markers of hypercoagulability, such as prothrombin fragment 1+2 (F1+2), thrombin-antithrombin complex (TAT), D-Dimer, or the endogenous thrombin potential (ETP), an indicator of the plasma’s potential to generate thrombin, has not been performed. We prospectively followed 113 pregnant women with (n = 11) and without (n = 102) FVL and measured F1+2, TAT, D-Dimer and the ETP at the 12th, 22nd and 34th gestational week as well as 3 months after delivery (baseline) in each subject. None of the women developed clinical signs of venous thromboembolism during pregnancy or postpartum. Pregnant women with and without FVL exhibited substantial activation of the coagulation and fibrinolytic system as indicated by a gradual increase of F1+2, TAT and D-Dimer throughout uncomplicated pregnancy up to levels similar to those found in acute thromboembolic events (p < 0.0001 by analysis of variance for each parameters). Levels of F1+2 and TAT were comparable between women with and without FVL, but levels of D-Dimer were significantly higher in women with FVL than in those without the mutation (p = 0.0005). The ETP remained unchanged in both women with and without FVL at all timepoints. Our data demonstrate a substantial coagulation and fibrinolytic system activation in healthy women with and without FVL during uncomplicated pregnancy. An elevated F1+2, TAT or D-Dimer level during pregnancy is not necessarily indicative for an acute thromboembolic event. The normal ETP in both women with and without FVL suggests that the capacity of the plasma to generate thrombin after in vitro activation of the clotting system is not affected by pregnancy. Higher levels of D-Dimer in women with FVL than in women with wildtype factor V at baseline as well as during pregnancy indicate increased fibrinolytic system activation in carriers of the mutation.